1998
DOI: 10.1002/(sici)1098-1136(199803)22:3<249::aid-glia4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Regional, developmental, and cell cycle-dependent differences in ?, ?, and ?-opioid receptor expression among cultured mouse astrocytes

Abstract: The diversity of opioid receptor expression was examined in astrocytes in low-density and nondividing (confluent) cultures from the cerebral cortex, hippocampus, cerebellum, and striatum of 1-day-old mice. μ, δ, and κ Opioid receptor expression was assessed in individual cells immunocytochemically, by using flow cytometry, and functionally by examining agonist-induced changes in intracellular calcium ([Ca 2+ ] i ). Significant spatial and temporal differences were evident in the pattern of expression of μ, δ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 54 publications
3
51
1
Order By: Relevance
“…It has been shown that acute morphine stimulation can induce calcium signaling El-Hage et al, 2005) and ERK phosphorylation (Belcheva et al, 2003), while prolonged exposure affected proliferation (Stiene-Martin et al, 2001) and proteomic profile (Suder et al, 2009) in primary astrocytes. The absence of direct transcriptional effects of morphine in astrocytes in the current study may be explained by the low level of l opioid receptors in our cultures, which is consistent with previous reports (Ruzicka et al, 1995;Stiene-Martin et al, 1998). Similarly, earlier studies have shown that a very low fraction of astrocytes in the striatum of adult mice express lopioid receptors (Stiene-Martin et al, 2001).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigsupporting
confidence: 92%
“…It has been shown that acute morphine stimulation can induce calcium signaling El-Hage et al, 2005) and ERK phosphorylation (Belcheva et al, 2003), while prolonged exposure affected proliferation (Stiene-Martin et al, 2001) and proteomic profile (Suder et al, 2009) in primary astrocytes. The absence of direct transcriptional effects of morphine in astrocytes in the current study may be explained by the low level of l opioid receptors in our cultures, which is consistent with previous reports (Ruzicka et al, 1995;Stiene-Martin et al, 1998). Similarly, earlier studies have shown that a very low fraction of astrocytes in the striatum of adult mice express lopioid receptors (Stiene-Martin et al, 2001).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigsupporting
confidence: 92%
“…In this study, we demonstrated that cortical purified astrocytes were markedly activated by METH. Opioid receptors are widely expressed by astrocytes, and the activation of m-opioid receptors can modulate programmed cell death (Stiene-Martin et al, 1998;Khurdayan et al, 2004). Unlike METH, however, MRP failed to induce the morphological change in cortical purified astrocytes (Narita et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, depending on the receptor type, β-FNA can exhibit agonist or antagonist activity (Holtzman, 1997;Sayre et al, 1984). Astroglia express all three opioid receptor types (, δ and κ) and these receptors are differentially expressed among brain regions (Ruzicka et al, 1995;Stiene-Martin et al, 1998). Also, age-related and cell-cycle-dependent variations in opioid phenotype can be observed at the cellular level (Stiene-Martin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Astroglia express all three opioid receptor types (, δ and κ) and these receptors are differentially expressed among brain regions (Ruzicka et al, 1995;Stiene-Martin et al, 1998). Also, age-related and cell-cycle-dependent variations in opioid phenotype can be observed at the cellular level (Stiene-Martin et al, 1998). However, morphine functions predominantly through MOR (Baumhaker et al, 1993;Stefano et al, 1996).…”
Section: Discussionmentioning
confidence: 99%